2017
DOI: 10.1021/acschemneuro.6b00325
|View full text |Cite
|
Sign up to set email alerts
|

Background Signal as an in Situ Predictor of Dopamine Oxidation Potential: Improving Interpretation of Fast-Scan Cyclic Voltammetry Data

Abstract: Background-subtracted fast-scan cyclic voltammetry (FSCV) has emerged as a powerful analytical technique for monitoring sub-second molecular fluctuations in live brain tissue. Despite increasing utilization of FSCV, efforts to improve the accuracy of quantification have been limited due to the complexity of the technique and the dynamic recording environment. It is clear that variable electrode performance renders calibration necessary for accurate quantification; however, the nature of in vivo measurements ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…To begin to address these issues, a recent study systematically evaluated how shifts in system impedance alter the position of peak redox current generated when using FSCV. 106 This important study demonstrates that the background voltammograms that are normally subtracted and discarded in FSCV contain a wealth of information that can be leveraged to enhance quantification. There is a critical need for a robust and user-friendly method of drift compensation in order to enhance accuracy in both the identification and quantification of chemical species using FSCV, particularly in longitudinal studies.…”
Section: Fscv: Under Construction…mentioning
confidence: 99%
“…To begin to address these issues, a recent study systematically evaluated how shifts in system impedance alter the position of peak redox current generated when using FSCV. 106 This important study demonstrates that the background voltammograms that are normally subtracted and discarded in FSCV contain a wealth of information that can be leveraged to enhance quantification. There is a critical need for a robust and user-friendly method of drift compensation in order to enhance accuracy in both the identification and quantification of chemical species using FSCV, particularly in longitudinal studies.…”
Section: Fscv: Under Construction…mentioning
confidence: 99%
“…As such, subtle alterations in the function of these modulators are thought to underlie the phenotypes of many disorders of the brain (Owens and Nemeroff ; Abi‐Dargham et al ; Volkow and Fowler ; Oades ; Muller et al ). To better understand the functional importance of messengers like serotonin in the brain, analytical measurements of neurotransmitters is a thriving and rapidly evolving field (Meunier et al ; Johnson et al ; Shen et al ). To this end, we have thus far focused on pioneering in vivo measurements of evoked and ambient serotonin using fast‐scan cyclic voltammetry (FSCV) and fast‐scan controlled adsorption voltammetry (FSCAV) at carbon fiber microelectrodes (CFMs) (Hashemi et al ; Abdalla et al ).…”
mentioning
confidence: 99%
“…Recent works from the Sombers' group have suggested that the FSCV current can be used as a predictor of electrode fouling and sensitivity to multiple analytes in situ (Roberts et al, 2013;Meunier et al, 2017). Furthermore, EIS has been considered a valuable technique to probe electrode conditions and biofouling (Wilks et al, 2012;Alba et al, 2015), as well as predict electrochemical FSCV performance, using equivalent circuit models of the electrode/solution interface (Roberts et al, 2013;Meunier et al, 2020).…”
Section: Evaluation Of Cfe Fouling In Vivo and Effect Of Tissue Exposmentioning
confidence: 99%